Genealogy and Orientation of the Islamic Modernist Movement in Indonesia: Case Study of the Muhammadiyah Renewal Movement - Takdir, Mohammad; Munir, Akhmad Sirojuddin (Journal of Al-Tamaddun, 2025)
This research elaborates on the genealogy and orientation of the Muhammadiyah renewal movement as one of Indonesia’s most prominent Islamic organizations. Muhammadiyah is an Islamic modernist movement that promotes reform in various fields, such as social, political, economic, educational, and religious. This research uses qualitative research to explore the genealogy and orientation of the Muhammadiyah renewal movement as the pioneer of the Islamic modernist movement in Indonesia. This research uses a library study to explore essential data about the Muhammadiyah renewal movement using a historical-sociological approach. Meanwhile, the data collection techniques used in this research are documentation techniques originating from books, research reports, and journal articles. The data analysis used is a descriptive analysis based on valid and up-to-date literature data. Meanwhile, the theory used to analyze the genealogy and orientation of the Muhammadiyah renewal movement is social mobilization theory. The results of this research indicate that (1) the genealogy of the Islamic modernist movement in the case of Muhammadiyah is motivated by problems associated with social crisis, moral crisis, education, religion, and the response to the development of Christianization in Indonesia (2) the orientation of the Muhammadiyah renewal movement is the creation of intellectual modernism, social modernism, and spiritual modernism among generations of Indonesian Muslims.